Methodical competence of teacher trainees in their written teacher certification examination - Bjedov, Vesna (Revija za elementarno izobraževanje, 2013)
The paper discusses methodical competence of teacher trainees in their written papers composed as part of their teacher certification examination. The aim of this discourse is to establish the existence of methodical competence of Croatian language teacher trainees in their written teacher certification examination. The paper focuses on the following categories: the application of theoretical methodical knowledge of basic sciences and special theoretical methodical knowledge, supporting theoretical knowledge and practical experience with examples, and finding references in literature on methodology. The research was conducted on 58 written papers of Croatian language teacher trainees in primary and secondary schools in the following counties: Istria, Primorje-Gorski Kotar, Lika-Senj, Zagreb, Međimurje, Varaždin, Osijek-Baranja, Brod-Posavina, Požega-Slavonia, and Virovitica-Podravina. Based on this research study it was established that Croatian language teacher trainees show methodical competence especially with regard to the application of theoretical methodical knowledge of basic sciences and special theoretical methodical knowledge and references in literature on methodology.
Keywords: competences; učitelji; methodical competences; pripravništvo; kompetence; examinations; Croatia; strokovni izpiti; Hrvaška